Macroalgal Diversity in Intertidal Zone of Mbuluk Beach, Gunungkidul, Indonesia: Keanekaragaman Makroalga di Zona Intertidal Pantai Mbuluk, Gunungkidul, Indonesia - Renada Oktavia; Arli Siti Nurlaila; Renisha Windy Puspita Sari; Alifia Nur Hidayah; Muhammad Ariq Alfito; Indira Amani Kurniawan; Valeria Nawang Riris Lintang Kaloka; Abdul Razaq Chasani (Talenta Publisher, 2025)
Mbuluk Beach is one of the new tourist beaches in Kemadang Village, Tanjungsari District, Gunungkidul Regency, D. I. Yogyakarta. Mbuluk Beach is a small beach which is characterised by a rocky substrate along the coastal area and overgrown with macroalgae. This research aims to study the diversity of macroalgae in the intertidal zone of Mbuluk Beach and determine the physicochemical parameters that influence their distribution and diversity. This research was conducted on October 21st, 2023. The method used was systematic sampling for collecting samples and directly measuring physicochemical parameters. The calculated index of species diversity used is Shannon-Wiener’s formula. The result showed that seventeen species of macroalgae were identified, consisting of six species from Chlorophyta, two species from Phaeophyta, and nine species from Rhodophyta. The macroalgal diversity index in the intertidal zone of Mbuluk Beach is 1.9, which means that the level of species diversity is moderate. The type of substrate which is mostly rocky substrate and the physicochemical parameters obtained, including air temperature (22°C), water temperature (21.3°C), pH (7.4), salinity (35.1 ppt), light intensity (5219.5 Lux), characterized the environmental conditions in which the identified macroalgae species were present in the intertidal zone of Mbuluk beach